Evaluating virtual reality technology in psychotherapy: impacts on anxiety, depression, and ADHD - Peng Wang; Xiaowen Ai; Xiyang Zhang; Fei Ma; Yan Zhuang; Suogang Wang (Frontiers in Psychiatry)
BackgroundMental health issues pose a significant challenge for medical providers and the general public. The World Health Organization predicts that by 2030, mental health problems will become the leading cause of global disease burden, highlighting the urgent need for effective mental health interventions. Virtual reality-cognitive behavioral therapy (VR-CBT) has emerged as a promising treatment for neuropsychiatric disorders, offering immersive and engaging therapeutic experiences.ObjectiveThis study aims to assess the advancements in applying virtual reality (VR) technology for diagnosing and treating mental illnesses such as anxiety, depression, and attention deficit hyperactivity disorder (ADHD). It also explores the integration of artificial intelligence (AI) with VR technology in mental health treatment and introduces the CBT-CHAT Treatment Framework to enhance cognitive behavioral therapy.MethodA systematic search was conducted across the databases of Google Scholar, PubMed, and Web of Science, followed by a scoping review. Duplicates were removed using the EndNote literature management software. Each article was then carefully read and evaluated for its research content, methodology, results, and contribution to the application of VR technology in mental health domains.ResultsThe search retrieved 686 articles, and after applying inclusion and exclusion criteria, 32 articles were ultimately selected. These articles covered the application of VR in anxiety, depression, and ADHD. The research results indicate that VR shows promising outcomes in the diagnosis, treatment, and rehabilitation of anxiety, depression, and ADHD, particularly in the diagnosis, treatment, and rehabilitation of ADHD.ConclusionThe previously published studies consistently demonstrate that VR is an effective tool for supporting the treatment of mental illnesses across various settings and recommend its incorporation into clinical practice.